Cost-Utility Analysis of Saxagliptin/Dapagliflozin Versus Gliclazide and Insulin Glargine: Economic Implications of the Outcomes of the CVD-Real Studies I and II - Enrico Torre; Giacomo Matteo Bruno; Sergio Di Matteo; Chiara Martinotti; Maria Chiara Valentino; Luigi Carlo Bottaro; Giorgio Lorenzo Colombo (SAGE Publishing, 2020)
Diabetes treatment cost represents an ever-growing problem. The adoption of new drugs in therapy, although they can guarantee an improvement in patient's quality of life, can meet obstacles when it involves an increase in costs. We decided to compare the costs and benefits of the new saxagliptin and dapagliflozin combination versus traditional therapies. Bodyweight loss and the sharp reduction in hypoglycemic episodes were the 2 main clinical outcomes that emerged from registered studies of saxagliptin and dapagliflozin compared with the sulfonylureas. These results, combined with the good cardiovascular risk profile, led to develop a cost-utility analysis. We aimed to show the economic value of this new association therapy. We carried out a cost-utility analysis from the Italian National Healthcare System (NHS) perspective, focused on direct costs related to the treatment and management of main diabetes complications. Utility scores adopted have been measured based on the patient's perception of weight changes. In light of the better durability profile of saxagliptin/dapagliflozin compared with gliclazide, we also considered a simulation scenario to assess the impact on costs of switching to basal insulin, starting from gliclazide and the fixed combination, respectively, and based on the related probabilities to switch. To assess the robustness of the results, a 1-way sensitivity analysis was performed by changing the main parameters by ±20%. Furthermore, the sensitivity of the results was tested considering the addition of a percent discount, because the purchase costs of drugs are usually subject to hidden discounts. We calculated the total direct annual cost per patient of saxagliptin/dapagliflozin versus gliclazide and insulin glargine for patients with type 2 diabetes mellitus not achieving glycemic control on metformin plus saxagliptin alone, dapagliflozin alone, or gliclazide at a lower dosage. Total treatment costs have been obtained adding the direct cost of the drug, needles, glycemic self-monitoring, hypoglycemic events, cardiovascular complications, and effect on consumption of other drugs. The total direct cost of saxagliptin/dapagliflozin fixed dose combination was €414.62 higher than gliclazide (€1.067.72 vs €653.10), and greater than basal insulin, with a difference of €166.99 (€1067.72 vs €900.72). Despite the higher annual direct total cost, the additional cost per quality-adjusted life year (QALY) gained, compared with gliclazide, has been €11 517, and €4639, when compared with insulin glargine in the base-case scenario, and the robustness of the results has been shown in the sensitivity analysis. The results of our cost-utility analysis, expressed as incremental cost-effectiveness ratios, were fully compliant with the threshold adopted for Italy. Then, saxagliptin/dapagliflozin can be considered a cost-effective oral hypoglycemic agent. The positive effect of this drug on the quality of life, induced by the bodyweight loss, has allowed this outcome, despite the higher annual cost per patient, mainly determined by the drug purchase cost.